Living with Fibromyalgia: A Phenomenological Study of Pain, Fatigue, and Coping - Rostami, Mehdi; Bulut, Sefa; Coelho, Olga; Riyono, Bagus (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This phenomenological study aims to explore the lived experiences of individuals diagnosed with fibromyalgia (FM), focusing on their experiences of pain, fatigue, and the coping mechanisms they employ to manage these symptoms. Employing a qualitative phenomenological approach, data were collected through semi-structured interviews with 25 participants who have been diagnosed with FM. Participants were recruited from various fibromyalgia support groups and clinics, ensuring a diverse representation in terms of age, gender, and duration of diagnosis. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis to achieve theoretical saturation. Three main themes were identified from the interviews: Pain, Fatigue, and Coping Mechanisms. Under the Pain theme, categories included the nature and characteristics of pain, its impact on physical function, and pain management strategies. The Fatigue theme comprised chronic exhaustion, cognitive fatigue, and its impact on daily activities. For Coping Mechanisms, emotional strategies, physical coping tactics, and social support were highlighted as key categories. These themes underscore the complex interplay between the physical symptoms of FM and the psychological and social strategies employed by individuals to manage their condition. The study highlights the pervasive and multifaceted nature of pain and fatigue in fibromyalgia, significantly impacting individuals' daily lives and functional abilities. It also reveals the importance of effective coping strategies, both adaptive and maladaptive, in managing these symptoms. These findings emphasize the need for a holistic and personalized approach to the management and support of individuals living with FM, incorporating both pharmacological and non-pharmacological interventions.